IMPLEMENTASI KEBIJAKAN PENDIDIKAN GRATIS TINGKAT PENDIDIKAN DASAR DAN MENENGAH DI KABUPATEN BULUNGAN PROVINSI KALIMANTAN UTARA (STUDI KASUS DI SMA NEGERI 1 TANJUNG SELOR) - M.Fachrizal Abubakar (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The research examines the Education Policy Implementation Guide Level Elementary And Secondary Education in Bulungan North Kalimantan (Case Study In SMA Negeri 1 Tanjung Selor). The result showed the overall picture that the Free Education Policy Implementation Level Elementary And Secondary Education in Bulungan North Kalimantan (Case Study In SMA Negeri 1 Tanjung Selor) has been used in accordance with the provisions and target groups BOSDA in SMA Negeri 1 Tanjung Selor. Although in terms of the amount received is not in accordance with the provisions, but the school felt greatly helped by BOSDA. Factors inhibiting the implementation of the Regional Regulation No. 13 Year 2014 concerning the implementation of the program of free education in primary and secondary education in Bulungan, complexity in the preparation of an accountability report that is due to the short period of preparation of accountability reports.